Pre- and post-operative evaluations of eight dogs following right nephrectomy due to Dioctophyma renale - Mesquita, L. R. [UNESP]; Rahal, Sheila Canevese [UNESP]; Faria, L. G. [UNESP]; Takahira, Regina Kiomi [UNESP]; Rocha, Noeme Sousa [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Oliveira, H. S. [UNESP] (Taylor & Francis Ltd, 2014)
Background: Dioctophyma renale is a large nematode distributed worldwide that may cause progressive and severe destruction of renal parenchyma.Objectives: The present study aimed to evaluate pre- and post-operatively dogs submitted to right nephrectomy due to D. renale and to assess the histopathological damage of the removed kidney.Animals and methods: Eight crossbred dogs, aged from 12 to 48 months that were unilaterally nephrectomized due to the presence of D. renale were evaluated. Physical examination, urinalysis, complete blood count, serum biochemistry, and abdominal ultrasound were performed immediately before and one month after nephrectomy. The nephrectomized right kidneys were submitted to macroscopic and microscopic evaluations.Results: Urinalysis preoperatively detected occult blood in all dogs and D. renale eggs in five cases. Complete blood count showed all parameters within the reference range, except one dog post-operatively. Serum biochemistry performed before and after surgery verified that urea, creatinine and sodium were within the reference range values in all dogs. Other findings varied among the dogs. The length and arterial resistive index mean values of the left kidney were similar pre- and post-operatively.Conclusions: Thus, the inconsiderable change in laboratory findings pre- and post-operatively was attributable to compensation by left kidney function for the removed abnormal right kidney. Right kidney histology revealed chronic nephropathy due to D. renale.Clinical importance: Imaging diagnosis should be performed on dogs suspected as carrying the disease or on those from an enzootic area since the laboratory findings are not specific except eggs in the urine.
Keywords: canine; kidney; histopathology; dog; nephrectomy; Dioctophyma renale